2017
DOI: 10.3389/fendo.2017.00278
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Progenitor Cells in Type 1 Diabetic Patients: Relation with Patients’ Age and Disease Duration

Abstract: ObjectivesCirculating endothelial progenitor cells (cEPCs) have been reported to be dysfunctional in diabetes mellitus (DM) patients, accounting for the vascular damage and the ensuing high risk for cardiovascular disease (CVD) characteristic of this disease. The aim of the present study was to evaluate the number of circulating cEPCs in type 1 DM (T1DM) patients, without clinical vascular damage, of different ages and with different disease duration.MethodsAn observational, clinical-based prospective study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
4
17
0
Order By: Relevance
“…In this study, we found a significant relationship between EPC counts and age. In a study of patients with type 1 diabetes, it was found that younger patients (age < 20 years) had significantly higher circulating EPC counts than adult patients (Arcangeli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found a significant relationship between EPC counts and age. In a study of patients with type 1 diabetes, it was found that younger patients (age < 20 years) had significantly higher circulating EPC counts than adult patients (Arcangeli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients with type 1 diabetes, it was found that younger patients (age < 20 years) had significantly higher circulating EPC counts than adult patients (Arcangeli et al., 2017). Disease duration has no effect on this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been carried out with MACs also, where young patients with type 1 diabetes mellitus have shown significantly higher levels of MACs compared to adult patients, and where a direct correlation was found between MAC number and disease duration, when greater than 10 years ( 38 ). The authors propose that the high levels of MACs in the young patients might protect vessels against endothelial dysfunction and damage and such protection would be less effective in older subjects, who had lower EPC numbers ( 38 ). In addition, older MACs were shown to be more susceptible to oxidative stress due to reduced activity of antioxidant proteins such as GPX1, thus rendering them vulnerable to apoptosis ( 38 , 39 ).…”
Section: Defective Epcs In Aging and Diabetesmentioning
confidence: 99%
“…DM decreased the number of circulating EPCs and impaired EPCs functional activity [10][11][12], which were associated with the development and poor prognosis of vascular disease [27,28]. The present study revealed the molecular mechanism underlying DM-induced EPCs dysfunction.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies demonstrated that endothelial progenitor cells (EPCs) were vital in endothelial reparation [6][7][8][9]. However, DM impaired EPCs function and decreased the circulating EPCs level in either patients or mice with diabetes [10][11][12]. Thus, preventing adverse vascular events was crucial to understanding the potential mechanism underlying EPC dysfunction in DM.…”
Section: Introductionmentioning
confidence: 99%